Matrix Vesicles as a Therapeutic Target for Vascular Calcification - Li, Tiantian; Yu, Hongchi; Zhang, Demao; Feng, Tang; Miao, Michael; Li, Jianwei; Liu, Xiaoheng (Frontiers in Cell and Developmental Biology, 2022)
Vascular calcification (VC) is linked to an increased risk of heart disease, stroke, and atherosclerotic plaque rupture. It is a cell-active process regulated by vascular cells rather than pure passive calcium (Ca) deposition. In recent years, extracellular vesicles (EVs) have attracted extensive attention because of their essential role in the process of VC. Matrix vesicles (MVs), one type of EVs, are especially critical in extracellular matrix mineralization and the early stages of the development of VC. Vascular smooth muscle cells (VSMCs) have the potential to undergo phenotypic transformation and to serve as a nucleation site for hydroxyapatite crystals upon extracellular stimulation. However, it is not clear what underlying mechanism that MVs drive the VSMCs phenotype switching and to result in calcification. This article aims to review the detailed role of MVs in the progression of VC and compare the difference with other major drivers of calcification, including aging, uremia, mechanical stress, oxidative stress, and inflammation. We will also bring attention to the novel findings in the isolation and characterization of MVs, and the therapeutic application of MVs in VC.